Inhibisi korosi baja dalam air laur mengandung sulfida menggunakan glutaraldehida - Larisa Deviyani; Isdiriayani Nurdin (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2006)
Most of steel corrosion on process equipment using seawater as utilities is due to corrosive seawater contaminants; one of which is sulfide. Corrosion control, which is commonly applied to steel in sulfide containing seawater, is chemical inhibition. In this research, the influence of H2S concentration on corrosion of steel in artificial seawater, and determination of the optimum doses of glutaraldehyde as corrosion inhibitor, are carried out by corrosion rate measurement according Tafel method; while prediction of inhibition mechanism is studied according to cyclic voltammetry method. The experimental result shows that steel is readily corroded in artificial seawater. Addition of H2S to artificial seawater increases corrosion rate. Glutaraldehiyde is an effective corrosion inhibitor for steel in seawater contaminated by H2S. The highest inhibition effectiveness on steel corrosion in seawater contaminated by 250 ppm H2S is 99.99%, which is obtained by adding of 80 ppm glutaraldehiyde. Generally, the oxidation reaction of steel in artificial seawater contaminated by H2S and inhibited with glutaraldehyde, is a one step irreversible reaction giving unstable product. Glutaraldehyde inhibits corrosion reaction through adsorption on steel surface, proven by reduction of corrosion product quantity.Keywords: Corrosion Inhibitor, Steel, Glutaraldehyde, Sulfide. AbstrakKorosi peralatan proses terbuat dari bajayang menggunakan air laut sebagai air utilitas disebabkan oleh kontaminan air laut yang bersifat korosif, salah satunya adalah sulfida. Pengendalian korosi baja dalam air laut mengandung sulfida dilakukan dengan penambahan inhibitor. Pada penelitian ini, untuk mengetahui pengaruh konsentrasi H2S dalam air laut terhadap korosi baja, serta menentukan dosis optimum glutaraldehida sebagai inhibitor korosi, dilakukan pengukuran laju korosi baja dengan metoda Tafel, dan perkiraan mekanisme inhibisi dengan metode voltameri siklik. Hasil percobaan menunjukkan bahwa baja terkorosi dalam air laut tiruan. Penambahan H2S dalam air laut tiruan meningkatkan laju korosi baja. Glutaraldehida efektif sebagai inhibitor korosi baja dalam air laut terkontaminasi H2S, dengan keefektifan inhibisi tertinggi adalah 99,99%, yang diperoleh dengan penambahan 80 ppm glutaraldehida ke dalam air laut tiruan yang mengandung 250 ppm H2S. Secara umum reaksi oksidasi baja dalam air laut tiruan terkontaminasi H2S dengan penambahan glutaraldehida berlangsung dalam satu tahap, merupakan reaksi irreversibel dengan produk reaksi yang bersifat tidak stabil. Inhibitor glutaraldehida menghambat korosi dengan cara teradsorbsi dipermukaan pelat baja, terbukti dengan penurunan kuantitas produk korosi.Kata Kunci: Inhibitor Korosi, Baja, Glutaraldehida, Sulfida